2014
DOI: 10.1007/s00348-014-1830-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of PIV to highlight possible errors in hot-wire Reynolds stress data over a 2D rough wall

Abstract: International audienceParticle image velocimetry (PIV) measurements are carried out in a turbulent boundary layer over a 2D rough surface consisting of transverse square bars. The aim of this work is to investigate a possible cause for the near-wall X-wire measurement errors observed on similar rough surfaces. The PIV measurements do not show the anomalous near-wall deficit of Reynolds stresses as measured with X-wires over the same surface. An extensive flow visualization analysis of the PIV data for a spacing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This paves the way for a proper comparison 1 3 121 Page 2 of 8 Luxton 1971; Kameda et al 1998), thus lending credence to the belief that the deficit in −�uv� near the wall is incorrect. Recently, using an extensive flow analysis of PIV data in a turbulent boundary layer over a rough wall made up of 2D square bars with a spacing between the bars of seven times the bar height, Djenidi et al (2014) observed that large outward motions instantaneously deviate from the mean flow direction by up to 50°. This supports the argument that the X-wire is inefficient for detecting these motions, particularly if the apex angle of the X-wire is not optimized for capturing strong flow ejections with large deviations, thus leading to a deficit in −�uv�.…”
Section: Introductionmentioning
confidence: 99%
“…This paves the way for a proper comparison 1 3 121 Page 2 of 8 Luxton 1971; Kameda et al 1998), thus lending credence to the belief that the deficit in −�uv� near the wall is incorrect. Recently, using an extensive flow analysis of PIV data in a turbulent boundary layer over a rough wall made up of 2D square bars with a spacing between the bars of seven times the bar height, Djenidi et al (2014) observed that large outward motions instantaneously deviate from the mean flow direction by up to 50°. This supports the argument that the X-wire is inefficient for detecting these motions, particularly if the apex angle of the X-wire is not optimized for capturing strong flow ejections with large deviations, thus leading to a deficit in −�uv�.…”
Section: Introductionmentioning
confidence: 99%